Allogeneic mesenchymal stromal cells overexpressing mutant human Hypoxia-inducible factor 1-α (HIF1-α) in an ovine model of acute myocardial infarction - Hnatiuk, Anna (2016)
Background-Bone marrow mesenchymal stromal cells (BMMSCs) are cardioprotective in acute myocardial infarction (AMI) because of release of paracrine angiogenic and prosurvival factors. Hypoxia-inducible factor 1-α (HIF1-α), rapidly degraded during normoxia, is stabilized during ischemia and upregulates various cardioprotective genes. We hypothesized that BMMSCs engineered to overexpress mutant, oxygen-resistant HIF1-α would confer greater cardioprotection than nontransfected BMMSCs in sheep with AMI. Methods and Results-Allogeneic BMMSCs transfected with a minicircle vector encoding mutant HIF1-α (BMMSC-HIF) were injected in the peri-infarct of sheep (n=6) undergoing coronary occlusion. Over 2 months, infarct volume measured by cardiac magnetic resonance (CMR) imaging decreased by 71.7±1.3% (P < 0.001), and left ventricular (LV) percent ejection fraction (%EF) increased near 2-fold (P < 0.001) in the presence of markedly decreased end-systolic volume. Sheep receiving nontransfected BMMSCs (BMMSC; n=6) displayed less infarct size limitation and percent LVEF improvement, whereas in placebo-treated animals (n=6), neither parameters changed over time. HIF1-α-transfected BMMSCs (BMMSC-HIF) induced angio-/arteriogenesis and decreased apoptosis by HIF1-mediated overexpression of erythropoietin, inducible nitrous oxide synthase, vascular endothelial growth factor, and angiopoietin-1. Cell tracking using paramagnetic iron nanoparticles in 12 additional sheep revealed enhanced long-term retention of BMMSC-HIF. Conclusions-Intramyocardial delivery of BMMSC-HIF reduced infarct size and improved LV systolic performance compared to BMMSC, attributed to increased neovascularization and cardioprotective effects induced by HIF1-mediated overexpression of paracrine factors and enhanced retention of injected cells. Given the safety of the minicircle vector and the feasibility of BMMSCs for allogeneic application, this treatment may be potentially useful in the clinic.